Pengembangan Semangka Dayun sebagai Produk Unggulan Melalui Indikasi Geografis untuk Perlindungan Hak Kekayaan Intelektual - Sukamarriko Andrikasmi; Ledy Diana; Mubarak Mubarak; Reny Fitri Yani; Hussein Al Muhtadeebillah; Dian Pratiwi; Siti Nurjanah; Fahrur Rozi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
This community service activity aims to encourage the development of Dayun Watermelon as a superior regional product while providing legal protection through the Geographical Indication (GI) scheme as a form of Intellectual Property Rights (IPR). Dayun Watermelon has unique taste, quality, and cultivation techniques that are passed down from generation to generation, so it has the potential to become a regional asset with high economic and cultural value. The implementation was conducted through socialization regarding the importance of IPR protection, technical training in preparing Geographical Indication documents, mentoring farmer groups in building institutions, and facilitating cooperation with local governments and related stakeholders. The results indicate an increase in farmer and community understanding regarding the benefits of Geographical Indication protection, the formation of a collective understanding to maintain product quality, and the initial steps in preparing IPR application documents. This activity is expected to strengthen the competitiveness of Dayun Watermelon, improve farmer welfare, and protect local identity through a sustainable IPR protection system.